PENGEMBANGAN MODEL PEMBELAJARAN INOVATIF BERBASIS KOMPETENSI - I Wayan Arka (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
The vision of National Education is the realization of the education system as a strong and authoritative social institution to empower all Indonesian citizens to develop into qualified human beings so that they are able and proactively respond to the ever-changing challenges. In connection with this vision, a set of principles was established to form the basis for implementing educational reform. The implication of this principle is a shift in the educational process from the teaching paradigm to the learning paradigm which gives more roles to students to develop the skills needed by themselves, the community, the nation and the State. Therefore we need a strategy and learning model that is in accordance with the quality standards of educators that have been set. Implementation of competency-based innovative learning models is learning done with the orientation of achieving students' competencies. Learning is faced in problem solving situations, so students become critical, creative, and able to solve the problems they face. Teachers need to design learning that is related to life problems or the context of students' lives. The teacher's role is as a facilitator, motivator and resource personKeywords: Learning Model, Innovative, Competency Based